Velasco Arias, Gonzalo (2023). Pensar la polarización - Jesús Navarro (Enrahonar: Quaderns de Filosofia, 2024)
Velasco Arias, Gonzalo (2023) Pensar la polarización Barcelona: Gedisa, 160 p. ISBN 9788419406163